Convergence of Bakubae Theological Values in Ambon Conflict Resolution, 1999-2024 - Burhanudin (Pascasarjana Universitas KH. Abdul Chalim, 2024)
This study seeks to reveal the process of resolving the Ambon conflict in 1999-2002 using a religious and cultural approach to resolution based on BakuBae theology. The spirit of peace that is built is a concept that originates from the basic values of religious and cultural theological teachings to become a meeting point (convergence) in a long process of political debate by moderate civil society together with the government and religious leaders, academies, latupatti, lower, gresroad, as social agents for ending the violence of the Ambon conflict. The construction of peaceful values based on religious technology and local culture is the key to strengthening the process of building a more permanent peace which was initiated politically by the Minister of Social Welfare and former Vice President Jusuf Kalla (JK) in Malino, South Sulawesi on 10-12 February 2002, which was then agreed upon by 70 religious representatives and gave birth to four BakuBae theological value systems (forgiveness, justice, solidarity and diversity).